The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1161/circimaging.115.003506
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism Diagnosed From Right Heart Changes Seen After Exercise Stress Echocardiography

Abstract: A 47-year-old black woman with no prior medical problems presented to the emergency department after a syncopal event associated with palpitations while walking. The patient noticed new onset of palpitations while walking that lasted about an hour. She subsequently had a syncopal episode. She denied dizziness, lightheadedness, dehydration, or seizure-like activity. Medications included antihistamines and oral contraceptives. On admission she was afebrile, heart rate 84 bpm, blood pressure 121/73 mm Hg, respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…In four of them (19%) RV dysfunction, septal shift, or pulmonary hypertension developed exclusively at exercise. Previous isolated case-report studies have shown RV dilation and pulmonary hypertension detected exclusively at exercise in patients with PTE [9,10]. The advantage of suspecting PTE lies on specific treatment available for it [1].…”
Section: Discussionmentioning
confidence: 98%
“…In four of them (19%) RV dysfunction, septal shift, or pulmonary hypertension developed exclusively at exercise. Previous isolated case-report studies have shown RV dilation and pulmonary hypertension detected exclusively at exercise in patients with PTE [9,10]. The advantage of suspecting PTE lies on specific treatment available for it [1].…”
Section: Discussionmentioning
confidence: 98%
“…Con respecto al diagnóstico mediante ecocardiografía de estrés de un TEP agudo son muy escasos los reportes publicados en la literatura 2,3 . En ambos el ecocardiograma basal era normal y con el esfuerzo desarrollaron datos de dilatación y sobrecarga de cavidades derechas, confirmando a posteriori el diagnóstico de TEP mediante angioTAC de arterias pulmonares, similar a lo acontecido en nuestro caso 2,3 .…”
Section: Discussionunclassified